Peningkatan Kesadaran Integrasi Teknologi Dalam Pembelajaran Bagi Guru Madrasah Aliyah Se-Kabupaten Lumajang Melalui Workshop Pengembangan Media Ajar Berbasis Android - Muh harawan Dimas jakaria (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Based on data from Ofcom, school-age children gadget usage is almost 100% from population. But this is little to no effort to use the gadgets as a learning media. This is partly because not all teachers are able to combine technology with learning, especially for teachers who are not in big cities such as Lumajang. Therefore, this community services activity was focused on mentoring in training and developing android learning media based on apache cordova for madrasah Aliyah teachers in Lumajang district. The method used in this activity is Participatory Action Research with workshop techniques and mentoring. This activity involved 50 teachers from various Madrasah Aliyah in Lumajang. The result of this activity is the increasing knowledge and ability of Madrasah Aliyah teachers in Lumajang in the development of innovative android-based learning media as evidenced by the positive response and realization of learning in the classroom using innovative learning media